Eradicating Women’s Surnames: Law, Tradition, and the Politics of Memory - Anthony, Deborah (Columbia Journal of Gender and Law, 2018)
English surname usage prior to the 17th century was quite variable, bearing little resemblance to the typical practices seen in modern-day England and the United States. Women at one time held individualized surnames reflecting their specific traits, occupations, or family relations; they often retained their names after marriage and passed them on to their husbands, children, and grandchildren. But these diverse surname practices eventually disappeared. The modern gendered practices became so entrenched and political that not only social forces but also legal ones sprang up to enforce them, with justifications referencing a naturally-ordered “tradition” so fundamental and absolute that it merited legal compulsion despite nearly a millennium of common law and empirical evidence to the contrary. The history of women’s surnames was entirely discarded and replaced with an alternate false tradition in the service of cultural and political ends that rooted itself so deeply it still remains one of the most commonly accepted gender-specific practices of modern times.